"This is my boy's health! Talk straight to me!" perspectives on accessible and culturally safe care among Aboriginal and Torres Strait Islander patients of clinical genetics services - Philippa Dalach; Ravi Savarirayan; Gareth Baynam; Julie McGaughran; Emma Kowal; Libby Massey; Misty Jenkins; Yin Paradies; Margaret Kelaher (BMC, 2021)
Abstract Background Aboriginal and Torres Strait Islander people do not enjoy equal access to specialist health services that adequately meet their needs. Clinical genetics services are at the vanguard of realising the health benefits of genomic medicine. As the field continues to expand in clinical utility and implementation, it is critical that Aboriginal and Torres Strait Islander people are able to participate and benefit equally to avoid further widening of the existing health gap. This is the first study to explore barriers to accessing clinical genetics services among Aboriginal and Torres Strait Islander people, which has been acknowledged as a key strategic priority in Australian genomic health policy. Methods A participatory design process engaged a majority-Aboriginal Project Reference Group and Aboriginal End-User Group. 63 semi-structured interviews were conducted with Aboriginal and/or Torres Strait Islander people who had accessed the government-funded clinical genetics service in Western Australia, Queensland or the Northern Territory between 2014 and 2018. The sample included patients, parents and carers. Participants were asked to recount their 'patient journey', from referral through to post-appointment and reflect on their perceptions of genetics and its implications for the health of themselves and their families. Analysis tracked chronological service engagement, followed by an inductive thematic approach. Results Barriers to access and engagement were present at each stage of the patient journey. These included challenges in obtaining a referral, long waiting periods, limited genetic literacy, absence of Aboriginal support services, communication challenges and lack of adequate psychosocial support and follow-up after attendance. Participants' overall experiences of attending a genetic health service were varied, with positive perceptions tied closely to a diagnosis being achieved. The experience of (and expectation for) recognition of cultural identity and provision of culturally safe care was low among participants. Unaddressed concerns continued to cause significant distress in some people years after their appointment took place. Conclusions There is significant scope for improving the care provided to Aboriginal and Torres Strait Islander people at clinical genetics services. Immediate attention to minimising logistical barriers, developing relationships with Aboriginal Community Controlled Health Services and providing practical and specific cultural safety training for practitioners is required at the service-level. Our findings strongly support the development of guidelines or policies recognising the collective cultural needs of Aboriginal and Torres Strait Islander people in relation to genomic health care.